A “Novel” Protocol for the Analysis of Hydroxycinnamic Acids in Leaf Tissue of Chicory (Cichorium intybus L., Asteraceae) - Meriem Bahri; Philippe Hance; Sébastien Grec; Marie-Christine Quillet; Francis Trotin; Jean-Louis Hilbert; Theo Hendriks (The Scientific World Journal)
A “novel” protocol is presented for easy and reliable estimation of soluble hydroxycinnamate levels in Cichorium intybus L. leaf tissue in large-scale experiments. Samples were standardized by punching 6 discs per leaf, and hydroxycinnamates were extracted by submerging the discs in 80% ethanol with 5% acetic acid for at least 48 h in the darkness at 4°C. Residual dry mass of the discs was used for a posteriori correction of compound levels. Chlorophyll was eliminated by chloroform, and the aqueous phases were transferred to microplates, dried, and dissolved in 50% methanol for HPLC analysis and storage. An HPLC program of 8 min was developed for the analysis of the extracts. Comparisons with extractions of liquid nitrogen powders indicated that the novel extraction method was reliable. No degradation of the major hydroxycinnamates—caftaric, chlorogenic, and chicoric acids—was observed, during maceration at ambient temperatures, or after storage for 1 year.